2018
DOI: 10.1523/jneurosci.3270-17.2018
|View full text |Cite
|
Sign up to set email alerts
|

Short-Term Plasticity Combines with Excitation–Inhibition Balance to Expand Cerebellar Purkinje Cell Dynamic Range

Abstract: The balance between excitation (E) and inhibition (I) in neuronal networks controls the firing rate of principal cells through simple network organization, such as feedforward inhibitory circuits. Here, we demonstrate in male mice, that at the granule cell (GrC)-molecular layer interneuron (MLI)-Purkinje cell (PC) pathway of the cerebellar cortex, E/I balance is dynamically controlled by short-term dynamics during bursts of stimuli, shaping cerebellar output. Using a combination of electrophysiological recordi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
35
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
2
1

Relationship

3
6

Authors

Journals

citations
Cited by 30 publications
(44 citation statements)
references
References 60 publications
2
35
0
Order By: Relevance
“…During the stimulus trains, EPSCs showed an initial strong facilitation followed by depression (Fig. 5A, B) (Bao et al, 2010;Grangeray-Vilmint et al, 2018;Dorgans et al, 2019). The sequence of short-term facilitation and depression was the more evident the higher the stimulation frequency, suggesting that frequency-dependent short-term synaptic dynamics could regulate transmission efficacy along the PF -SC pathway (Mapelli et al, 2010).…”
Section: Frequency-dependent Short-term Dynamics At Parallel Fiber -Smentioning
confidence: 96%
“…During the stimulus trains, EPSCs showed an initial strong facilitation followed by depression (Fig. 5A, B) (Bao et al, 2010;Grangeray-Vilmint et al, 2018;Dorgans et al, 2019). The sequence of short-term facilitation and depression was the more evident the higher the stimulation frequency, suggesting that frequency-dependent short-term synaptic dynamics could regulate transmission efficacy along the PF -SC pathway (Mapelli et al, 2010).…”
Section: Frequency-dependent Short-term Dynamics At Parallel Fiber -Smentioning
confidence: 96%
“…Finally, and most importantly, the cellular mechanism of this short-term trial-by-trial learning is still unclear and how it correlates with long-term learning is unknown (Kimpo et al, 2014). Short-term plasticity of parallel fiber synapses and dendritic excitability plasticity may also be candidate mechanisms (Rancz and Häusser, 2006; Mathy et al, 2009; Ohtsuki et al, 2012; Regehr, 2012; Grangeray-Vilmint et al, 2018).…”
Section: Graded Error Signals In Cerebellar Learningmentioning
confidence: 99%
“…At the input stage of the cerebellar cortex, a strategy based on the heterogeneity of STP across MF-GC synapses provides a mechanism for coding multisensory events at the level of single GCs (Chabrol et al, 2015). Also, differences in the profile of STP across synapses involved in the direct excitatory pathway or in the FFI microcircuit control the inhibitory/excitatory balance and shape Purkinje cell discharge (Grangeray-Vilmint et al, 2018). GCs which are the most numerous neurons in the brain, segregate in clonally related subpopulations (Espinosa and Luo, 2008).…”
Section: Introductionmentioning
confidence: 99%
“…Following compound stimulations of clusters of GCs or beams of parallel fibers (PFs), it was shown that GC-BC synapses depress during high-frequency stimulation while GC-SC synapses facilitate (Bao et al, 2010). By controlling the spatiotemporal excitability of PC (Bao et al, 2010), and potentially by shaping the inhibitory/excitatory balance (Grangeray-Vilmint et al, 2018), target cell–dependency of STP at the input stage of the FFI pathway must have important functional consequences for cerebellar output. However, target cell–dependency of STP at GC-MLI synapses is challenged by different experimental findings.…”
Section: Introductionmentioning
confidence: 99%